DOCUMENTED RECORDS OF ASH-COLORED CUCKOO (Coccycua cinerea) IN AMAZONIAN PERU - ANGULO, Fernando Raúl (2018)
Ash-colored Cuckoo (Coccycua cinerea) it is considered a hypothetical species for Peru and there are no documented records of its presence within the country. It is considered to be a rare austral migrant to the lowlands of the southwest Peruvian Amazon. It is considered a vagrant in the northern Peruvian Amazon. Here we report four documented records of the species from the southern Peruvian Amazon and confirm its occurrence in the country. We further discuss the seasonality of the records and the species’ status within Peru and propose to change its status from Hypothetical to rare austral migrant.